Analisis Penerapan Projek Penguatan Profil Pelajar Pancasila di Sekolah Dasar - Sari, Tika; Ayuningsih, Tri Cahya (Indonesian Journal of Islamic Elementary Education, 2025)
In an effort to realize the Pancasila Student Profile, the Independent Curriculum integrates the Pancasila Student Profile Strengthening Project (P5) as part of project-based learning that is relevant to real life. SDN 028/IV Jambi City has implemented P5 systematically, starting from planning, implementation, to assessment. However, in its implementation, various challenges are still found that need to be explained in order to ensure the effectiveness of this program in improving the quality of education. This study aims to analyze the implementation of P5 at SDN 028/IV Jambi City using qualitative descriptive methods to provide an in-depth picture of the successes and obstacles faced. Data collection techniques include observation, interviews, and documentation. Data are analyzed through data reduction, data presentation, and verification. The results of the study indicate that the implementation of P5 in grade IV has gone well and according to the guidelines. The structure of P5 includes: (1) Planning, including the formation of time, identification of school readiness, determination of character dimensions, themes, timelines, modules, learning objectives, topics, activity flows, and assessments; (2) Implementation, including introduction and contextualization, P5 actions, project closing with celebration of results, and partner involvement; (3) Assessment and reporting, including collection, processing, analysis, and reporting of results; (4) Evaluation and follow-up, in the form of strengthening character and good habits through collaboration with parents. P5 actions are able to strengthen character, especially global diversity and critical thinking.